Building the Capacity of Family Day Care Educators to Promote Children's Social and Emotional Wellbeing: Results of an Exploratory Cluster Randomised-Controlled Trial. Issue 2 (May 2015) - Davis, Elise; Gilson, Kim-Michelle; Christian, Rahila; Waters, Elizabeth; Mackinnon, Andrew; Herrman, Helen; Sims, Margaret; Harrison, Linda; Cook, Kay; Mihalopoulos, Cathrine; Marshall, Bernie; Flego, Anna; et al.
THIS PAPER PRESENTS THE results of an exploratory cluster randomised-controlled trial that was used to pilot Thrive, a capacity-building program for family day care (FDC) educators. Participants were educators and coordinators from one FDC service in Melbourne, Australia. Data collection consisted of a survey including information on costs, an in-home quality of care observation and process evaluation. Data was collected over 12 months (2011–2012), at baseline and one, six and 12 months post-intervention. Positive caregiver interaction scores increased over time for the intervention group: F (3, 51.69) = 3.08, p < 0.05, and detached interaction scores decreased over time: F (3, 51.19) = 2.78, p < 0.05. Educators' knowledge and confidence in children's social and emotional wellbeing showed no significant change. Thrive gives important information about the challenges FDC educators face and is relevant to implementing changes in their education and support. For a program like Thrive to be successful in engaging educators, a stronger framework for supporting additional learning activities at both the FDC organisational and scheme level is warranted.